Aspectos sócio-históricos da substituição do vêneto pelo português nas zonas urbana e rural de Alfredo Chaves - Espírito Santo: o papel da escola - Fiorin, Marcio Favero (2019)
Alfredo Chaves was one of several municipalities of Espírito Santo colonized by Italian immigrants, mainly from the Veneto Region, who arrived from 1877, bringing with them their culture and language. However, the growing contacts between immigrants and their descendants with Portuguese speakers led to the replacement of “vênetas” varieties, primarily in the urban area and, finally, in the rural areas. Given this scenario, this study investigates the process of “vêneto” replacement in two localities of Alfredo Chaves - the city and the district of Santa Maria do Ibitiruí -, analyzing the performance of social factors for such occurrence, especially the school. To achieve this goal, in addition to documentary and bibliographic research, interviews were conducted with descendants of Italian immigrants living in both locations and with education professionals who worked and / or who work there. Analyzes were based on the Linguistic Contact theory, using contributions from authors such as Weinreich (1970 [1953]), Appel and Muysken (1996), Montrul (2013), etc. The results show that the nationalist policies implemented during the first government of Getúlio Vargas (1930 1945) favored Brazilian culture and were crucial for the imposition of the Portuguese language on Vêneto´s varieties. The testimonies collected also demonstrate that the educational system has acted in favor of the spread of Vargas nationalist laws in the past. At present, the normative teaching of Portuguese contributes by excluding linguistic variation in classrooms, culminating in situations of discrimination by teachers and students themselves, who speak Portuguese with the influence of the vêneto of language. Given these results, we conclude that supportive work is needed for school agents, through continuing education with them, so that cultural and linguistic diversity is respected and valued in communities colonized by immigrants, not only in Alfredo Chaves, as of the whole state of the Espírito Santo/BRA.